2001
DOI: 10.1111/j.1469-445x.2001.tb00036.x
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneously hypertensive rats exhibit altered cardiovascular and neuronal responses to muscle contraction

Abstract: We examined the cardiovascular and ventrolateral medullary neuronal responses to muscle contraction in the spontaneously hypertensive rat (SHR) and normotensive Wistar-Kyoto rat (WKY) control. Cardiovascular, respiratory and ventrolateral medullary neuronal responses to muscle contraction evoked by tibia1 nerve stimulation were recorded. SHRs exhibited significantly larger drops in arterial pressure compared to WKYs in response to muscle contraction (P C 0.05). Basal ventrolateral medulla neuronal discharge ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2002
2002
2009
2009

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
(43 reference statements)
0
1
0
1
Order By: Relevance
“…Previous studies using rats reported that the blood pressure response to static contraction or to muscle stretch elicited no change (34), an increase (2,19,32), or a decrease (15,22,32). These different responses were attributed to the different anesthetics, which include pentobarbital (2,19,32), chloral hydrate (2,19), halothane (27), and ␣-chloralose (16,22,34). Only two studies used a decerebrate preparation, and both showed consistent pressor reflex response to muscle contraction (23,27).…”
mentioning
confidence: 98%
“…Previous studies using rats reported that the blood pressure response to static contraction or to muscle stretch elicited no change (34), an increase (2,19,32), or a decrease (15,22,32). These different responses were attributed to the different anesthetics, which include pentobarbital (2,19,32), chloral hydrate (2,19), halothane (27), and ␣-chloralose (16,22,34). Only two studies used a decerebrate preparation, and both showed consistent pressor reflex response to muscle contraction (23,27).…”
mentioning
confidence: 98%
“…Em relação ao músculo estriado, Kramer e Waldrop 36 realizaram um estudo da resposta neuronal em SHR, durante contração muscular isométrica, e obtiveram o seguinte resultado: tanto os SHR quanto os WKY, apresentaram significante redução da pressão arterial, evocada pela contração muscular, via nervo tibial; porém, esta redução ocorreu muito rapidamente e não se manteve por toda a contração. Em WKY a média foi de -21.1 ± 1.8 mmHg, enquanto que nos SHR foi de -33.2 ± 1.9 mmHg.…”
Section: -Estudos Morfológicos E Funcio-nais Em Shrunclassified